PENGARUH KUALIFIKASI PENDIDIKAN TERHADAP PENEMPATAN KERJA APARATUR SIPIL NEGARA (ASN) - Fatmawati Mujiati; Sugiantiningsih Agung; Ronald Umbas (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
Effective and efficient governance is demanded in this competitive globalization era. Work performance of bureaucrats that still does not meet people’s expectation is still experienced by the people. That problem can be reduced by  the implementation of the ministerial regulation on civil servants and bureaucratic reform number:Kep/33/M.PAN/7/2011. It regulates the placement of civil servants and has been applied by the Office for Housing Facilities Bali Province. Its bureaucrats were placed in the positions according to their knowledge, educational background, and expertise and skills so that they work and serve the people better. The writer used perspctective qualitative approach to identify the phenomenon.  Primary and secondary data were collected through observation and interview, and analysed with interactive data analysis technique (Miles, Hubernam, and Saldana 2014). Based on the analysis, it can be concluded that the indicators that were used to assign a civil servant in a certain position in this office were knowledge, skills, and expertise.